(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The following paper aims to quantify the bedload transport in the Paraná river in the Porto São José cross section (22°45’52”S; 53°10’34”W), between Porto Primavera and Itaipu dams, Brazil. In the used method, the bedload transport is estimated from the height and the displacement of the dunes along a longitudinal profile. The results were compared with those obtained from classical bedload transport equations. In the Porto São José cross section, the estimated average bedload transport applying the Dune Displacement Method (DDM) was 3,157 t d-1, which corresponds to an average annual bedload transport of 1,152,325 t yr-1. Applying the Van Rijn equation the average bedload transport was calculated in 2,830 t d-1 (1,032,950 t yr-1), while using the Engelund-Fredsøe equation the average bedload transport found was 3,135 t d-1 (1,144,378 t yr-1). The obtained values using different methods presented some coherence each other, which means that these results can be used as a starting point to establish bedload transport estimations in the Upper Paraná river.